TANTANGAN DAN UPAYA PENGELOLAAN STRES SELAMA PANDEMI COVID-19: STUDI KASUS GURU SMP XYZ DI TANGERANG [CHALLENGES AND EFFORTS TO MANAGE STRESS DURING THE COVID-19 PANDEMIC: A CASE STUDY OF XYZ MIDDLE SCHOOL TEACHERS IN TANGERANG] - Risti Irawan; Natalia Astri Christyani; Brigita Saras Andriani; Irene Putri (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
Sudden changes due to the Covid-19 pandemic have created new problems in the implementation of teaching that can cause teachers to experience stress with physical, psychological, and behavioral symptoms. This case study explores the theme of stress management by teachers of SMP XYZ in Tangerang. The method used is a qualitative approach with observation, collecting data using a questionnaire to ten teachers to determine the appropriate research subjects, and conducting in-depth interviews with two teachers to explore and describe what makes them have different stress levels even though they are in the same organization. The results of the study can be concluded that the challenge of managing stress faced by teachers is the gap between their competencies and the demands of work according to the existing context, such as time management and class management. Their efforts are coping strategies by taking time off, changing mindsets, and increasing competence.